2019
DOI: 10.21203/rs.2.12812/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-PD-1 antibody decreases tumour-infiltrating regulatory T cells

Abstract: Background: There are many types of therapies for cancer. In these days, immunotherapies, especially immune checkpoint inhibitors, are focused on. Though many types of immune checkpoint inhibitors are there, the difference of effect and its mechanism are unclear. Some reports suggest the response rate of anti-PD-1 antibody is superior to that of anti-PD-L1 antibody and could potentially produce different mechanisms of action. On the other hand, Treg also express PD-1; however, their relationship remains unclea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Subsequent research has substantiated Tregs' role in facilitating tumor cell immune evasion. Notably, Yoshida et al reported that anti-PD-1 antibodies reduced Tregs infiltration in osteosarcoma, correlating with tumor growth delay and prolonged survival (Yoshida et al, 2020). Biller et al's research on canine osteosarcoma demonstrated an increase in Tregs and a concurrent reduction in the CD8 + T cells to Tregs proportion, correlating with diminished survival times, further emphasizing the importance of Tregs in facilitating tumor immune escape (Biller et al, 2010).…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%
“…Subsequent research has substantiated Tregs' role in facilitating tumor cell immune evasion. Notably, Yoshida et al reported that anti-PD-1 antibodies reduced Tregs infiltration in osteosarcoma, correlating with tumor growth delay and prolonged survival (Yoshida et al, 2020). Biller et al's research on canine osteosarcoma demonstrated an increase in Tregs and a concurrent reduction in the CD8 + T cells to Tregs proportion, correlating with diminished survival times, further emphasizing the importance of Tregs in facilitating tumor immune escape (Biller et al, 2010).…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%
“…Recently, immunotherapy has made breakthroughs in the field of cancer therapy. Immune checkpoint inhibitors, such as PD-1, PD-L1, and CTAL4, have shown significant antitumor effects on various cancers (7)(8)(9). Additionally, these immune checkpoint inhibitors have been shown to play substantial roles in the treatment of OS.…”
Section: Introductionmentioning
confidence: 99%